Tontemboan Affixes Notes in Teaching English Tenses - Tirza Kumayas (International Journal of Applied Business and International Management, 2021)
Teaching English language is a big challenge in Minahasa. Students are still unable to master or even comprehend English even after eleven years learning the language at primary and secondary levels. This research entitled â€œTontemboan Affixes Relates to English Tensesâ€ aims to identify, classify and describe the affixes and analyze the similarities and differences of affixes used in both languages, English and Tontemboan. This research used descriptive method, which includes preparation, collecting the data, and analyzing the data. The result showed that some affixes in Totemboan language have different functions of affixes in English. Simple present tense functions the habitual action by adding maâ€™ before the morpheme, following the verb. The present continuous tense which is formed by adding maâ€™ as prefix has a global meaning. Past continuous tense indicated by adding the prefix maâ€™ and simple past tensi indicated by adding a base prefix and infix with the initials are consonant.